2015
DOI: 10.1589/jpts.27.1585
|View full text |Cite
|
Sign up to set email alerts
|

The effects of modified constraint-induced therapy combined with mental practice on patients with chronic stroke

Abstract: [Purpose] The purpose of this study was to investigate the effects of the modified constraint-induced therapy (mCIT) combined with mental practice (MP) on patients with chronic stroke. [Subjects] The subjects were 26 patients with chronic stroke. [Methods] Patients were randomly assigned to the mCIMT + MP group or the MP group. All subjects were administered mCIT consisting of (1) therapy emphasizing affected arm use in functional activities 5 days/week for 6 weeks and (2) 4 hours of restraint of the less affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
(34 reference statements)
1
17
0
6
Order By: Relevance
“…The EG subjects showed larger improvements in the FM, BBT, and MAL-QOM than the CG subjects. These results are consistent with those of other studies in which MP was combined with other interventions for the affected UE 25 , 26 , 27 , 28 , 29 , 30 ) . MP has been shown to independently produce neural changes 25 ) .…”
Section: Discussionsupporting
confidence: 92%
“…The EG subjects showed larger improvements in the FM, BBT, and MAL-QOM than the CG subjects. These results are consistent with those of other studies in which MP was combined with other interventions for the affected UE 25 , 26 , 27 , 28 , 29 , 30 ) . MP has been shown to independently produce neural changes 25 ) .…”
Section: Discussionsupporting
confidence: 92%
“…The Korean version of the Modified Barthel Index was used to evaluate activities of daily living (ADL) function 12 ) . The Korean version of the Modified Barthel Index is a reliable, valid tool for measuring the ADL of patients in Korea and has a maximal score of 100 indicating complete independence in ADL.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Kim et al employed MI-based rehabilitation combined with physical training in stroke patients, and identified benefits to upper extremity motor function as measured using the FMA and the Wolf Motor Function Test [ 62 ]. Further, a study of 26 chronic stroke patients identified a benefit to upper extremity MI when used in conjunction with modified CIMT [ 63 ], and another investigation utilized MI with physical practice to enhance hand recovery [ 64 ]. Well-summarized in another review [ 65 ], studies by Page et al indicated that MI improved function in the impaired upper limb when combined with conventional physiotherapy [ 66 ], task-oriented training [ 67 ], and CIMT [ 68 ].…”
Section: For Post-stroke Rehabilitationmentioning
confidence: 99%